2016
DOI: 10.1007/s11695-016-2475-7
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Weight Loss and Weight Regain after Gastric Bypass Surgery—Postoperative Status of Energy Intake, Eating Behavior, Physical Activity, and Psychometrics

Abstract: BackgroundSuboptimal weight loss (SWL) and weight regain (WR) after gastric bypass surgery (GB) remains poorly understood.ObjectivesThis study aims to compare GB patients experiencing SWL or significant WR (SigWR) with successful controls, regarding postoperative food intake, eating behavior, physical activity (PA), and psychometrics.MethodsForty-nine patients with >1 year post-surgery were classified as either experiencing SWL (excess body weight loss, EWL, <50%, n = 22) or SigWR (total weight regain ≥15%, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
73
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 54 publications
4
73
1
11
Order By: Relevance
“…Therefore, bariatric patients are advised to engage in regular physical activity [8][9][10][11]. Previous studies indicate that low physical activity after bariatric surgery is related to less weight loss and more weight regain [12][13][14], though more recent studies question whether weight loss is positively influenced by adherence to a healthy lifestyle with regular physical activity [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, bariatric patients are advised to engage in regular physical activity [8][9][10][11]. Previous studies indicate that low physical activity after bariatric surgery is related to less weight loss and more weight regain [12][13][14], though more recent studies question whether weight loss is positively influenced by adherence to a healthy lifestyle with regular physical activity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Emotional eating, in which patients report to eat more in response to emotions, has been linked to less weight loss in two studies [17,18]. However, others did not support this association [12,13]. Studies on self-reported external and restrained eating show the same conflicting results; some suggest a negative effect on weight change, while other studies show no effect [12,13,17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, both previous cluster models lack the inclusion of emotion dysregulation and disinhibited eating behaviors for subtyping prebariatric patients, although the predictive value of these intrapersonal factors for postbariatric weight outcome was suggested (Amundsen, Strømmen, & Martins, ; Mack et al, ; Marek, Ben‐Porath, Dulmen, Ashton, & Heinberg, ; Wedin et al, ). This study aimed to provide a fine‐grained analysis of prebariatric subtypes by additionally taking emotion dysregulation and disinhibited eating behaviors into account.…”
Section: Introductionmentioning
confidence: 99%
“…É um procedimento cirúrgico comum para pacientes com obesidade mórbida. Os efeitos em longo prazo do BGYR estão bem documentados, tanto em termos de perda de peso, melhoria ou resolução de comorbidades relacionadas à obesidade, como fatores de risco, bem como com a melhoria da qualidade de vida (QV) (Amundsen et al, 2017). Entretanto, a recidiva de peso ocorre em aproximadamente 20% dos pacientes e constitui uma questão preocupante (Meguid et al, 2008).…”
unclassified
“…Este índice foi registrado em ficha específica, desenvolvida por Sales, para facilitar a tabulação dos dados. Códigos e Descrições de Perda Dentária 5…”
unclassified